Analysis and Optimisation of High Pressure Die Casting Parameters to Achieve Six Sigma Quality Product Using Numerical Simulation Approach - Suraj R. Marathe; Dr. Carmo E. Quadros (International Journal of Engineering and Management Research, 2021)
A numerical simulation approach is proposed to predict the optimal parameter setting during high pressure die casting. The contribution from the optimal parameters, the temperature, showed more influence on the casting quality than the other parameters. This study’s outcome was beneficial for finding the solution for casting defects that occurs due to incorrect setting of process parameters in die casting. Thus, a combination of numerical optimisation techniques and casting simulation serves as a tool to improve the casting product quality in die casting industries. This paper aims to analyse and optimise critical parameters like injection pressure, molten metal temperature, holding time, and plunger velocity, contributing to the defects. In this research paper, an effort has been made to give optimal pressure, temperature, holding time, and plunger velocity parameters using ProCAST simulation software that uses finite element analysis technology. Numerical analysis for optimising the parameters by varying the temperature of molten metal, injection pressure, holding time, and plunger velocity, concerning solidification time at hot spots, is an essential parameter for studying the defect analysis in the simulated model.